Before & after the economic crisis 2008: Changes in Pay Structure of Top UK Bank Executives - Kumar, Subrat (2011)
The main idea of my dissertation is to determine the effect of firm’s performance on the remuneration package during the financial crisis 2008. The form & pay structure of top executives of UK banks has been subjected to major changes within the financial crisis. There has been a complexity in executive pay because of the number of different pay components were associated with the pay structure. My study will explore different remuneration components such as Executive Share Options: The lot size of share options called as ESO, LTIPs Long term incentive Plans: A profit sharing scheme attached to the changing earning per share, an individual performance based cash bonus which is paid annually & various non –cash benefits. A sample of top 40 UK banks was chosen for data analysis (financial year 2005 to 2010).